An empirical study on the model of self-efficacy and organizational citizenship behavior transmitted through employee engagement, organizational commitment and job satisfaction in the Thai automobile parts manufacturing industry - Khahan Na-Nan; Suteeluck Kanthong; Jamnean Joungtrakul (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This research aims to study the direct and indirect influence of self-efficacy on organizational citizenship behavior transmitted through employee engagement, organizational commitment and job satisfaction, and to examine employee engagement, organizational commitment and job satisfaction as partial or full mediators. The study samples were 400 employees in the automobile parts manufacturing industry. The study instruments used by previous researchers were applied and back translation was conducted on all questionnaire items. Content validity and reliability was then tested prior to using them for data collection. Direct and indirect influences and mediators were analyzed with the Hayes Model 81 using the PROCESS Program. Results revealed that self-efficacy had a direct influence on organizational citizenship behavior with statistical significance, with an indirect influence transmitted through employee engagement, organizational commitment and job satisfaction. Employee engagement, organizational commitment and job satisfaction functioned as partial mediators between self-efficacy and organizational citizenship behavior with statistical significance. The model was based on the theory of self-efficacy to express organizational citizenship behavior. However, the study results showed that employee engagement, organizational commitment and job satisfaction play roles as mediators in transmission of effective organizational citizenship behavior. Therefore, these mediators are important factors that can accurately explain organizational citizenship behavior.
Keywords: 650; self-efficacy; organizational citizenship behavior; employee engagement; organizationalcommitment; job satisfaction